Your leadership moment democratizing leadership in an age of authoritarianism - Martin, Eric R. (Coral Gables Mango Publishing, 2020)
Influence Your Organization and Lead Change Anyone can be a leader. You don't have to be a CEO or work in a management position to have influence. Your Leadership Moment provides practical tools, techniques and inspiration to discover your leadership potential. It combines personal and real-world anecdotes with a framework for leadership that can help anyone learn to lead. Anyone can be an influencer. Author and leadership expert Eric Martin has brought leadership development to the lives of hundreds of thousands of people in 146 countries. Eric's work draws on Adaptive Leadership, an unconventional and somewhat provocative leadership practice developed at Harvard by Drs. Ron Heifetz and Marty Linsky and by Alexander Grashow, with whom he has mentored and worked. Your Leadership Moment teaches Martin's expansion on Adaptive Leadership in a way everyone can understand. Anyone can change the world. Your Leadership Moment is for real people who seek to create consequential, meaningful change despite having little to no authority or power. In this book, you will discover: What a Leadership Moment is and the key concepts of Adaptive Leadership How to stop solving the wrong problems perfectly and start solving the right problems creatively How to think politically and mobilize others to help you make real, positive change
Keywords: Leadership